2000
DOI: 10.1095/biolreprod63.6.1905
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tumor Necrosis Factor α and Its Type I Receptor in Luteal Regression: Induction of Programmed Cell Death in Bovine Corpus Luteum-Derived Endothelial Cells

Abstract: The role of tumor necrosis factor alpha (TNF alpha) and its type I receptor (TNFRI) in structural luteolysis was investigated. A semiquatitative reverse-transcription polymerase chain reaction (RT-PCR) was used to characterize the pattern of TNFRI mRNA expression within the corpus luteum (CL) throughout the estrous cycle and its cellular distribution. Increase in TNFRI mRNA levels was recorded both in regressed luteal tissue and in CL of cows injected with prostaglandin F(2 alpha). All three major cell types c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
122
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(138 citation statements)
references
References 45 publications
7
122
2
Order By: Relevance
“…These types of cells may have different regulatory mechanisms of cell death and the high expression of this protease suggests an important role of caspase-2 in the apoptotic death of these cells. Several studies demonstrated apoptosis of endothelial cells and suggested its activation through the tumor necrosis factor-a pathway (Friedman et al 2000, Pru et al 2003. Moreover, even though caspase-2 was the first mammalian apoptotic caspase identified (Kumar et al 1994, Wang et al 1994, little is known about its function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These types of cells may have different regulatory mechanisms of cell death and the high expression of this protease suggests an important role of caspase-2 in the apoptotic death of these cells. Several studies demonstrated apoptosis of endothelial cells and suggested its activation through the tumor necrosis factor-a pathway (Friedman et al 2000, Pru et al 2003. Moreover, even though caspase-2 was the first mammalian apoptotic caspase identified (Kumar et al 1994, Wang et al 1994, little is known about its function.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that initiator caspases are activated following direct association with death domain proteins. Interestingly, immune cells as well as cytokines were shown to play a role in regulating luteal function in rats, mice, cows, and women (Brannstrom & Friden 1997, Terranova & Rice 1997, Friedman et al 2000. Moreover, during luteolysis, macrophages are attracted and infiltrate in the CL, increasing the local production of cytokines (Brannstrom et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TNF-a has an inhibitory effect on progesterone secretion in bovine luteal cells (37) and high TNF-a bioactivity has been observed in the PGF 2a -treated ovine corpus luteum (38). The TNF type I receptor is dominantly expressed in luteal endothelial cells (39). TNF receptor mRNA is induced in regressing luteal tissues and TNF may be a paracrine accelerator of luteal regression.…”
Section: Discussionmentioning
confidence: 99%
“…The different sensitivities of each cell type to TNF may be due to the difference in secretory products between LECs and LSCs. Progesterone secreted by LSCs has been shown to inhibit cell death in both LECs [17] and LSCs [29]. On the other hand, endothelin-1 (ET-1), a vasoactive peptide secreted by LECs, induces luteolysis in the bovine CL [30,31].…”
mentioning
confidence: 99%